Evaluation of the Effectiveness of Organic and Mineral Fertilization (NPK) in Improving the Vegetative and Productive Traits of Strawberry (Fragaria × ananassa) - Hassan, Noor Alhuda Hameed; Basheer, Rawaa Abd; Al-Alosi, Nasr Shukri Drar (Universitas Muhammadiyah Sidoarjo, 2025)
Ruminant The study was conducted in an unheated plastic greenhouse at the University of Tikrit (2022–2023) to evaluate the effect of organic and mineral fertilizers on strawberry (Fragaria × ananassa) productivity. Organic treatments included mushroom waste (M1), poultry manure (M2), and a control, combined with three NPK mineral fertilizer levels (0, 0.75, and 1 g L⁻¹). A randomized complete block design (RCBD) with three replications was used, and data were analyzed using L.S.D at the 0.05 probability level. Results showed that M1 produced the highest number of leaves (31.19 leaves plant⁻¹), compared to M2 (28.59) and the control (27.69). For mineral fertilization, 1 g L⁻¹ resulted in 30.25 leaves plant⁻¹, higher than 0.75 g L⁻¹ (26.22), while 0 g L⁻¹ gave 30.94. No significant interaction was found between organic and mineral fertilization for this trait. Average leaf area showed no significant differences among organic treatments (32.78–35.11 cm²) or mineral levels (33.89–34.67 cm²). Leaf nitrogen (0.996–1.334%) and phosphorus (0.11699–0.12213%) contents also showed no significant variation. In contrast, leaf potassium content was significantly affected. M2 recorded the highest value (1.643%), followed by M1 (1.375%), while the control gave the lowest (1.028%). For mineral fertilization, 0 g L⁻¹ (1.433%) outperformed 0.75 (1.363%) and 1 g L⁻¹ (1.303%). A significant interaction was observed for potassium content, with L.S.D values confirming the combined influence of organic and mineral fertilization.